Asymmetric organocatalytic synthesis of quaternary α-hydroxy phosphonates: en route to α-aryl phosphaisoserines1. Issue 19 (7th March 2015) - Serrano, Inmaculada; Monge, David; Álvarez, Eleuterio; Fernández, Rosario; Lassaletta, José M.
<x xml:space="preserve">Abstract</x> The dual activation of acyl phosphonates and formaldehyde tert-butyl hydrazone by a BINAM-derived bis-urea catalyst is the key to achieve high reactivities and enantioselectivities in the synthesis of densely functionalized quaternary α-hydroxy phosphonates.